Effects of natural and commercial diets on growth, reproductive performances and embryogenesis of zebrafish Danio rerio (Dhaka University Journal of Biological Sciences, 2017)
This study evaluated the effects of five diets (diet 1: Dried tubifex, diet 2: Artemia, diet 3: Artemia and commercial pellet feed, diet 4: Spirulina and commercial pellet feed; diet 5: commercial pellet feed) on growth, reproductive performances and embryogenesis of zebrafish Danio rerio for a period of 62 days. Significantly higher specific growth rate was found in diet 5 when compared with diet 1 but no significant difference was observed between diet 2, 3, 4 and 5. Mean weight and length gain were significantly greater in zebrafish fed diet 5 than diets 1 ‐ 4. While 100% survival was found in diet 4, the lowest level was 90.26 ± 1.06% in diet 1. Mean spawning success was significantly higher in zebrafish fed diet 5 than in those fed diets 1 ‐ 4. Mean fertilization and hatching rates were higher in the fish fed diet 3 ‐ 5 than in diets 1 and 2. Zebrafish consumed commercial pellet feed only resulted in more viable offsprings and grown better. Results suggested that commercial pellet is suitable in zebrafish culture for maximum growth and production of viable offspring in laboratory condition.Dhaka Univ. J. Biol. Sci. 26(2): 159-166, 2017 (July)